A new species of Miliusa (Annonaceae) from the Western Ghats of Karnataka, India - Page, Navendu; Nerlekar, Ashish Nitin (Phytotaxa, 2016)
Within Magnoliales, Annonaceae is the most species-rich family (Chatrou et al. 2012). Miliusa Leschenault ex De Candolle (1832: 213) is placed in tribe Miliusae, subfamily Malmeoideae, according to the recent infrafamilial classification (Chatrou et al. 2012). Chaowasku et al. (2014) provided insights into the evolutionary relationships of tribe Miliusae, and Chaowasku & Keßler (2013) reconstructed the phylogeny of Miliusa with four well-supported clades. Miliusa is distributed across the Austro-Malesian region with most species exhibiting a restricted distribution to certain areas (Mols & Kessler 2003). Species known from India exhibit a high degree of endemism (Kundu 2006).